2001
DOI: 10.2337/diacare.24.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Meal-Related Dosing With Repaglinide Facilitates Glycemic Control in Therapy-Naive Type 2 Diabetes

Abstract: OBJECTIVE— This double-blind randomized placebo-controlled parallel group study assessed the efficacy and safety (with particular regard to body weight and hypoglycemia) of repaglinide when used in a flexible mealtime dosing regimen in a situation close to everyday clinical practice. RESEARCH DESIGN AND METHODS— A total of 408 patients with type 2 diabetes considered poorly controlled by diet, but without a history of previous antidiabetic medication, were randomized to receive 0.5 mg repaglinid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
1
4

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(25 citation statements)
references
References 14 publications
0
20
1
4
Order By: Relevance
“…In contrast to those receiving longer-acting insulin secretagogues such as sulfonylureas, patients treated with repaglinide are free to vary their meal pattern from two to four main meals daily and are also able to vary the timing of meals without impairing efficacy or augmenting the risk of hypoglycemia (12). Previously reported studies involving placebo or sulfonylureas as comparators have established the efficacy of repaglinide in improving glycemic control as being at least equivalent to that of conventional oral hypoglycemic agents (13,14).…”
mentioning
confidence: 99%
“…In contrast to those receiving longer-acting insulin secretagogues such as sulfonylureas, patients treated with repaglinide are free to vary their meal pattern from two to four main meals daily and are also able to vary the timing of meals without impairing efficacy or augmenting the risk of hypoglycemia (12). Previously reported studies involving placebo or sulfonylureas as comparators have established the efficacy of repaglinide in improving glycemic control as being at least equivalent to that of conventional oral hypoglycemic agents (13,14).…”
mentioning
confidence: 99%
“…23 In a study performed mainly in Caucasians, treatment with repaglinide (0.5-1.0 mg/meal) for 4 months significantly improved glycaemic control compared with baseline values and placebo, reducing the mean HbA 1c level by 1.1%. 24 Following the present study, the authors plan to evaluate the efficacy and safety of repaglinide administered two or three times daily at doses > 0.25 mg. In the present study, repaglinide therapy was as effective as results reported for glimepiride or glibenclamide therapy, [25][26][27] therefore, we also hope to evaluate the effectiveness of a two-or three-times-daily repaglinide regimen after switching from sulphonylurea treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The maximum dose should not exceed 4 mg before each meal; the dose should be skipped if the meal is missed [93]. Hypoglycaemia is the most common side-effect [94]. Natiglinide Natiglinide (Starlix) is a very short-acting glucose-lowering drug which appears to have its effect on the fi rst phase of insulin release rather than the late phase of insulin release [95].…”
Section: Repaglinidementioning
confidence: 99%